Organizational improvement and accountability : lessons for education from other sectors - Stecher, Brian M.; Kirby, Sheila Nataraj, 1946- (Rand Corp., 2004)
The No Child Left Behind Act (NCLB) is a performance-based accountability system built around student test results. The accountability system comprises explicit educational goals, assessments for measuring the attainment of goals and judging success, and consequences (rewards or sanctions). But the mechanisms through which the system is intended to work are not well understood. The authors examined five accountability models: two from the manufacturing sector (the Malcolm Baldrige National Quality Award Program and the Toyota Production System (TPS)), a performance incentive model used in the evaluation of job training programs for the poor, accountability in the legal sector, accountability in health care as shown by clinical practice guidelines, use of statistical risk-adjustment methods, and the public reporting of health performance measures. Although education faces unique challenges, the authors conclude that educators can learn much from these other sectors. The Baldrige, TPS, and the clinical practice guidelines suggest the importance of focused institutional self-assessment, understanding school and district operations as a production process, being able to develop and apply a knowledge base about effective practice, and empowering participants in the process to contribute to improvement efforts. The job training and risk-adjustment models and the legal and health care accountability models provide specific guidance on how to enhance system-wide accountability in education by broadening performance measures; making sure performance goals are fair to all students and schools; developing standards of practice in promising areas; and encouraging professional accountability.